Are Analytics Skills in Curriculum Aligned with Skills in Job Description? A Knowledge Graph Approach - Cherrington, Emma; Kim, Yong Seog (International Journal of Engineering and Management Research, 2024)
Recently, many academic institutions in the Intermountain West Region of USA update their traditional IS programs with various data analytics and data sciences courses. To evaluate whether newly incorporated contents are appropriate to prepare students as data scientists or data analysts, we compare core analytical skills emphasized in current data analytics and information systems (DAIS) curriculum with analytical skills in 11,225 job advertisements for data analysts or scientist positions. We found that job descriptions source presents the importance of application of specific skills to various business settings while curriculum source focuses on the conceptual and theoretical skills along with fundamental skills such as SQL. Based on our findings, we suggest that courses should address not only technical skills, but also soft skills to make informed decisions and turn them into business decisions through real application scenarios.